The Relationship of Illustrative Content In Flipbook Type of E-Book As An Illustrative Learning Media In Immune System With Reading Test Results Using Fry Graphics - Vania Nur Azizah; Widowati Budijastuti (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2020)
Illustrative learning media are all things that support the learning of students to obtain knowledge, skills or attitudes that are supported by appropriate illustrations. Illustrations generally take the form of pictures or videos. Some illustrations have supporting texts or as supporting texts themselves. This study aimed to analyze the relationship between illustrated content and readability in the supporting text of the flipbook type of e-book on immune system material. This research was a development study using the ASSURE model. As many as 34.7% of the illustrated content has supporting texts with a high school level of readability. Whereas 65.3% of the illustrative content cannot be analyzed about readability because of supporting texts that less than 100 words.